Broom's legal maxims (New Delhi, 2012)
Maxims are an established principle or proposition of law universally admitted as being just and consonant with reason, are part of the general customs or common law of the land. Broom's Legal Maxims first published in 1845 and numerous subsequent editions later, this treatise has now morphosised into its eleventh edition and has been well entrenched globally as an authoritative referencer. Endeavour has been made to preserve its original elementary essence and render the book, in its present form, accurate and useful. Redundant or obsolete matter has been expunged, the void been replaced by illustrations from the most recent cases. Along with latest case law, care has been taken to add several new and important maxims. Revised with an exhaustive treatment of Indian case law it is reasonably expected to prove alike serviceable to the practitioner as well as to the student
Keywords: Legal maxims-England